Operation Planning of the Elective Patients in an Orthopedic Surgery Department - Clavel, Daniel; Mahulea, Cristian; Albareda, Jorge; Silva, Manuel (Jornada de Jóvenes Investigadores del I3A, 2017)
This paper considers the operation scheduling and planning of elective patients in the Orthopedic Department of the “Lozano Blesa” Hospital in Zaragoza. We assume an ordered list of patients that should be planned for surgery. We propose a mixed linear integer programming problem to obtain a utilization rate of 80% per room. The results are tested on some real data from the hospital and some simulation results are provided.